Penguatan Soft Skill: Kapabilitas e-Commerce dan Laporan Keuangan Formal Bagi Pelaku Usaha di Kecamatan Pegandon: Strengthening Soft Skills: E-Commerce Capabilities and Formal Financial Reports for Business Players in Pegandon District - Sijabat, Rauly; Meiriyanti, Rita; Fathurachman, Chadyan; Ilham, Ratih Milati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Digital technology enables the growing development of online shopping. This also makes it possible for each seller to market their products or services with a wider range and costs that are not as expensive as conventional ones. Pegandon District has many business actors or MSMEs. The GRDP growth rate in Pegandon District has not recovered after the COVID-19 pandemic. One way to increase the GRDP growth rate is to increase the capability of business actors in selling or distributing their products. One of the product sales distribution channels is e-commerce. This training activity is related to marketing in utilizing e-commerce. Therefore, training on the use of e-commerce is not only to increase sales, business actors are also able to expand their product introduction. In addition, this service activity also provides training on preparing simple financial reporting. It is hoped that through the financial reporting that is owned, business actors can access capital from formal financial institutions